Therapeutic insects - Qamaruz Zaman, Faridah; Seng, Tzer Ying; Yap, W. K. (Universiti Putra Malaysia Press, 2013)
To some, insects invoke an uncomfortable feeling; phrases like creepy crawlies come to mind. But as the saying goes, don't judge a book by its cover; and so it is with insects. The ubiquitous cockroach (Blatta orientalis Linnaeus, Periplaneta americana Linnaeus, Periplaneta P. australasiae Fabricius) can be used to detoxify, soothe down blemishes, carbuncles and swellings, and reduce the poison if bitten by snake or insects. The cockroach is dried and the wings and feet discarded before use.